On the probability of estimating a deterministic component in the local level model - Harvey, A; Shephard, N (Blackwell Publishing, 1990)
A local level model has a deterministic level when the signal-to-noise ratio q is zero. In this paper we investigate the properties of the maximum likelihood estimator of q, paying particular attention to the case where its true value is zero. These properties are shown to be crucially dependent on the initial conditions employed.